MRSA bacteraemia in patients on arrival in hospital: a cohort study in Oxfordshire 1997-2003. - Wyllie, D; Peto, T; Crook, D (2005)
OBJECTIVE: To describe the incidence and determinants of methicillin resistant and methicillin sensitive Staphylococcus aureus (MRSA and MSSA) bacteraemia in patients presenting to acute hospitals. DESIGN: Anonymised record linkage study with information from hospital information systems and microbiology databases. SETTING: One teaching hospital and one district general hospital in Oxfordshire. PARTICIPANTS: All patients admitted to a teaching hospital 1 April 1997 to 31 March 2003 and to a district general hospital 1 April 1999 to 31 March 2003. MAIN OUTCOME MEASURES: Detection of MRSA and MSSA from blood cultures taken during the first two days of admission to hospital. RESULTS: In the teaching hospital, there were 479 patients with MSSA and 116 with MRSA bacteraemia admitted from the community. Among this group, which comprised 24% of all hospital MRSA cases, 31% (36 cases) of patients had been admitted to renal, oncology, or haematology services for intensive day case therapy. The 69% remaining were most commonly patients admitted as medical or surgical emergencies. At least 91% had been in hospital previously; the median time since discharge was 46 days. About half of cases were in patients in whom MRSA had not been isolated before. Similar epidemiology was observed in the district general hospital. CONCLUSION: Diagnostic algorithms and policies on use of antibiotics need to reflect the fact that a quarter of hospital MRSA cases occur in patients who have previously been in hospital and are subsequently readmitted.